Serological Evidence That SARS-CoV-2 Has Not Emerged in Deer in Germany or Austria during the COVID-19 Pandemic - Andres Moreira-Soto; Christian Walzer; Gábor Á. Czirják; Martin H. Richter; Stephen F. Marino; Annika Posautz; Pau De Yebra Rodo; Gayle K. McEwen; Jan Felix Drexler; Alex D. Greenwood (Microorganisms, 2022)
Spillover of severe acute respiratory syndrome coronavirus type 2 (SARS-CoV-2) to North American white-tailed deer (Odocoileus virginianus) has been documented. However, it is unclear if this is a phenomenon specific to North American deer or is a broader problem. We evaluated pre and pandemic exposure of German and Austrian deer species using a SARS-CoV-2 pseudoneutralization assay. In stark contrast to North American white-tailed deer, we found no evidence of SARS-CoV-2 exposure.